SALOON: a platform for selecting and configuring cloud environments. (13th January 2015) - Quinton, Clément; Romero, Daniel; Duchien, Laurence
Summary: Migrating legacy systems or deploying a new application to a cloud environment has recently become very trendy, because the number of cloud providers available is still increasing. These cloud environments provide a wide range of resources at different levels of functionality, which must be appropriately configured by stakeholders for the application to run properly. Handling this variability during the configuration and deployment stages is known as a complex and error‐prone process, usually made in an ad hoc manner. In this paper, we proposeSALOON, a software product lines ‐based platform to face these issues. We describe the architecture of theSALOON platform, which relies on feature models combined with a domain model used to select among cloud environments a well‐suited one.SALOON supports stakeholders while configuring the selected cloud environment in a consistent way and automates the deployment of such configurations through the generation of executable configuration scripts. This paper also reports on some experiments, showing that usingSALOON significantly reduces time to configure a cloud environment compared with a manual approach and provides a reliable way to find a correct and suitable configuration. Moreover, our empirical evaluation shows that our approach is effective and scalable to properly deal with a significant number of cloud environments. Copyright © 2015 John Wiley & Sons, Ltd.